PENGENDALIAN PERSEDIAAN BAHAN BAKU DALAM PROSES PRODUKSI DENGAN MENGGUNAKAN METODE ECONOMIC ORDER QUANTITY (EOQ) - Elia Rahayu R; Nor Norisanti; Acep Samsudin (IPM2KPE, 2019)
The purpose of this study is to control the supply of raw materials using the Economic Order Quantity (EOQ) method in Tahu Nugraha Jaya Sukabumi UKM. The data analysis method used is quantitative descriptive to describe and describe the data to be examined and then processed using EOQ. This study uses the EOQ method to determine the total inventory cost. The data needed in this study are the number of purchases of raw materials, the amount of use of raw materials, storage costs, and ordering costs. The results of this study indicate that by applying the EOQ method can further optimize the supply of raw materials by minimizing raw materials with increased inventory. With the application of the Economic Order Quantity (EOQ) method it shows more efficient than conventional methods of the company. Conclusions, seen from the difference in the TIC of the two methods, the more efficient method is the Economic Order Quantity (EOQ) method that is equal to 244,392.94 while the calculation used by the company is 374,325. so that it can be obtained that there is a difference between the Company TIC and the EIC method TIC. Keywords: Raw Material Inventory, Production Process